Public Expenditure and Revenue Causality Pattern in Nigeria - Ojelabi, Sunday Adeyemi; Bulama, Mohammed; Aruwa, Suleiman A. S. (Advances in Social Sciences Research Journal, 2022)
Government expenditure remains an important instrument utilised in the process of development. It plays a pivotal role in the functioning of any economy at almost all stages of growth and development. The expenses incurred will provide the necessary infrastructures such as health care, educational and social security services etc. Funds spent on the provision of infrastructures are basically sourced from taxes, fines, royalties, borrowings and grants from the states, national and international governments. This study is on Nigeria public expenditure and revenue for the period of 2010-2020, data were collected for eleven years and were analyzed using statistical package E-view 10. The study revealed that fiscal synchronization and tax and spend have positive and significant effects on government expenditure. While spend-revenue and spend and tax were found to be negative and insignificant on government expenditure in Nigeria. Based on the findings, the study concluded that federal government revenue, tax and spend and fiscal synchronization among the independent variables were statistically significant at 5% level of significance in the short run. In the long run, spend-revenue and spend and tax also turned out to be statistically significant. The study recommended that spend and tax of the country should cautiously be under watch to ensure that government should first make expenditure decision then adjust the tax policy and revenue in a way that it can go with the expenditure of the country. As for spend-revenue,government should always keep her expenditure under control by making sure that her expenditure change does not have any significant change on the revenue.